Eksistensi Perempuan di Era Demokrasi Perspektif Al-Qur'an dan Hadits - Nurhasanah Nurhasanah (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2013)
Controversy hits female involvement at various responsible positions in an era democratizes to be still happening. Because that happening spar available sentence and traditions like what does forbidden glimpse involvement femaling to gets action at democratizes era as responsible position of public or politics responsible position. Amongst those is al Ahzab’s letter about instructions to sentence 33 females for stays on the house and Bukhari’s Hadith is about the history of female leadership. ‘s sentences al-Qur ‘an and the Prophet’s said. If understood by comprehensively’s style and contextual actually does not block female existence in various and also responsible positions at age democratizes the which have no absolute authority.